Persepsi Masyarakat Terhadap Pentingnya Pendidikan Tinggi Untuk Kaum Perempuan - Suparno Suparno; Mira Hastin; Ni Kadek Sri Sumiartini; Dwi Pratiwi Lestari; Antonius Rino Vanchapo; Sabil Mokodenseho (Departement of Mathematics Education, 2023)
This study aims to describe the community's views on women who are highly educated and describe the community's perception of the importance of higher education for women in Dusun Baru Village, Siulak Sub-district. This research is descriptive qualitative research. The subject of this research is the community, the data collection methods in this research are observation, interview and documentation. The data sources used in this research are primary data sources and secondary data sources. The results found in the study are that the community views positively on highly educated women and hopes that they can apply their knowledge to the community and there are still people who think that women are not important to have a higher education on the grounds that their nature is in the kitchen but many people think that higher education is important for women because one day they will become educators for their children.